PENGEMBANGAN BAHAN AJAR MEMBACA BERORIENTASI KOOPERATIF TIPE CIRC DI KELAS IV SEKOLAH DASAR - Sry Apfani (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the importance of developing learning materials that can improve students' reading skill. Based on the above, developed learning materials oriented learning model of cooperative type CIRC. The purpose of developing this instructional material is to produce a valid, practical, and effective reading material. Type of research is research development . The development model is a 4-D model consisting of definitions, design, development, and disseminate. The result of validity test was valid with average value 3.35. The result of observation of the implementation of RPP states that the teaching material is practical with an average value of 90.90. In the effectiveness test stage, the average result obtained 92.33 and as many as 19 students from 20 people total reach Minimum Criteria completeness (KKM). Based on these results, it can be concluded that the reading material oriented cooperative learning model type CIRC in class IV Primary School that has been produced can be declared valid, practical, and effectiveKeywords: Development of Learning Materials, Reading, CIRC